Bounded Odd Inverse Pareto Exponential Distribution: Properties, Estimation, and Regression - Suleman Nasiru; Abdul Ghaniyyu Abubakari; Irene Dekomwine Angbing (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce a new three-parameter distribution defined on the unit interval. The density function of the distribution exhibits different kinds of shapes such as decreasing, increasing, left skewed, right skewed, and approximately symmetric. The failure rate function shows increasing, bathtub, and modified upside-down bathtub shapes. Six different frequentist estimation procedures were proposed for estimating the parameters of the distribution and their performance assessed via Monte Carlo simulations. Applications of the distribution were illustrated by analyzing two datasets and its fit compared to that of other distributions defined on the unit interval. Finally, we developed a regression model for a response variable that follows the new distribution.